Regulatory and legal basis of Ukraine’s investment policy in the field of higher education (Educational Dimension, 2020)
Elaboration and implementation of investment programs for the development of modern universities, cooperation with the business sector, public investment aimed at modernization of the educational environment, implementation of grants, etc. can now be considered as structural components of investment activities of higher education institutions in the context of strategic planning. Therefore, the process of active reform of the educational sector of Ukraine and its integration into the European educational space require a review of approaches, methods and forms of management of education and educational institutions, in particular on investment policy. The purpose of the study is to analyse and summarize the legislative aspects of introduction of the investment programs for the development of higher education institutions as an element of state educational policy. The subject of the study is the regulatory framework for investment activities of higher education institutions in Ukraine in the implementation of investment programs for their development as an element of state educational policy. The following research methods were used: terminological analysis (definition of the conceptual apparatus of the research), systematization of normative legal acts (study of normative provision and state of the researched problem), classification method (ranging of normative legal acts by branches of human activity). The practical importance of the study is in description of the current state of regulatory and legal support of Ukraine's investment policy in higher education. As a result of the study, we concluded that the investment activity of higher education institutions is determined by laws and subsidiary laws that regulate general aspects of Ukraine's investment policy at the state level and insufficiently regulate the development of investment opportunities at the institutional level. There is no concept of investment and investment activity in the regulations in the field of higher education at all. However, at the present stage of development of the studied branch it is important to specify the provisions of regulations and scientific concepts of Ukrainian investment policy for higher education. Thus, the analysis of regulations on investment activities of higher education institutions and the search for weaknesses in them will help improve the current legislation of Ukraine, identify priority areas for investment in education at the institutional level and consolidate investment opportunities of higher education institutions.